Reproductive studies on the carpet clam Paphia textile (Paratapes textilis) (Gmelin 1791) (Family: Veneridae): a guide of aquaculture management along the Egyptian coasts of the Red Sea and Suez Canal - Marwa I. Farghaly; Tamer El-Sayed Ali; Hanan M. Mitwally; Fatma A. Abdel Razek (BMC Zoology, 2023)
Abstract Background Most aquatic biota's reproductive biology and life cycle are essential to the sustainable management and development of coastal ecosystems and aquaculture. The bivalve Paphia textile (Gmelin 1791), also known as Paratapes textilis, has an economic value in Indo-Pacific waters, including the Red Sea and the Suez Canal lakes, the Egyptian coasts. However, P. textile suffers from extensive fishing and exploitation. Aim The present work aims to study the Paphia textile's reproductive cycle on the Egyptian coasts of the Red Sea for the first time. It helps to manage and develop the coastal ecosystems and aquaculture. Methodology Samples were collected monthly from two saline lakes in the Suez Gulf from December 2019 to November 2020. As part of the comprehensive research study, sex ratio, condition index, sexuality, histological analysis of gonads, shell size, and gonad index were used to investigate the reproductive cycle. Results The results reveal a male-biased sex ratio, possibly due to anthropogenic stressors. The Paphia textile is dioecious. No hermaphrodite cases were observed in the studied specimens. The condition index in winter and spring indicates periods dominated by mature individuals. Five reproductive maturity stages were assigned for both P. textile males and females. Due to the simultaneous development of several developmental stages monthly throughout the sampling year, warm water may be responsible for non-sequential gametogenic cycles. As measured environmental parameters correlate with maturity stages, temperature, salinity, and chlorophyll a play important role in gonad growth. The size at first sexual maturity at which 50% of the Paphia textile population reached maturity ranged from 28.60 to 31.50 mm for females, and between 31.70 and 34.10 mm for males. As the gonad index increases during the ripe stages, this index decreases during the resting, spawning, and spent phases. Conclusions The findings suggest the most suitable temperature for aquaculture spawning is between 20 °C and 30 °C in subtropical waters. Fishing should generally be prohibited at sizes less than 28.60 mm for better management and sustainability of this valuable aquatic resource on the Egyptian coasts of the Red Sea.